2015
DOI: 10.1007/s11999-015-4419-2
|View full text |Cite
|
Sign up to set email alerts
|

What Is the Most Useful Questionnaire for Measurement of Coping Strategies in Response to Nociception?

Abstract: Background There are several measures of coping strategies in response to nociception. These measures all correlate highly both with each other and with symptom intensity and magnitude of disability in patients with upper limb illness. This study aims to determine if distinct measures of coping strategies in response to nociception address the same underlying aspect of human illness behavior. Questions/purposes Our primary study question was: is there one common aspect of human illness behavior measured by (1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
66
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(72 citation statements)
references
References 32 publications
5
66
0
Order By: Relevance
“…In addition, the PROMIS 1 pain interference and the QuickDASH ask similar questions regarding the ability to engage in activities of daily living, with one focusing only on the effect of pain (eg, pain interference) and the other asking about symptoms and ability to engage in daily upper limb tasks (QuickDASH). In a prior study, Kortlever et al [14] found that measures of catastrophic thinking, self-efficacy about pain, and pain interference were all highly correlated, and they all correlated with the Quick-DASH. However it is unclear whether this indicates that limitations attributable to pain strongly reflect coping strategies or simply that most limitations are attributable to pain.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In addition, the PROMIS 1 pain interference and the QuickDASH ask similar questions regarding the ability to engage in activities of daily living, with one focusing only on the effect of pain (eg, pain interference) and the other asking about symptoms and ability to engage in daily upper limb tasks (QuickDASH). In a prior study, Kortlever et al [14] found that measures of catastrophic thinking, self-efficacy about pain, and pain interference were all highly correlated, and they all correlated with the Quick-DASH. However it is unclear whether this indicates that limitations attributable to pain strongly reflect coping strategies or simply that most limitations are attributable to pain.…”
Section: Discussionmentioning
confidence: 92%
“…Prior research has identified that depression and pain interference are important psychological factors associated with disability in patients with upper extremity illness, opening the door to opportunities to decrease disability through teaching coping skills aimed at improving mood and pain-related mindset [14,29]. Social factors such as feeling cared for, perceiving that others are available to help with tangible tasks, and the ability to see the positives in stressful situations like illness and pain, are important resiliency factors that buffer the effect of stress.…”
Section: Discussionmentioning
confidence: 99%
“…Pain interference questions were adapted from the publically available Patient Reported Outcomes Measurement Information System (PROMIS) instruments. 33 The PROMIS instruments facilitate patient communication regarding outcomes related to injury or illness 34,35 and are useful in evaluating pain, disability, and quality of life in patients with amputations involving the upper extremity 36 and lower extremity. 37 Because shortened pain inventories have been shown to be roughly equivalent or slightly more effective than more exhaustive inventories in detecting patient-reported pain scores, 38 our questionnaire was fashioned to simplify reporting, decrease interviewee fatigue, and optimize response rate.…”
Section: Methodsmentioning
confidence: 99%
“…Pain interference (PI), or the extent to which pain interferes with accomplishing goals, has a strong influence on perceived disability among hand and wrist patients 11 and can be efficiently quantified using the PROMIS PI CAT. 12 PROMIS PI scores independently predicted inferior PROMIS PF and UE CAT scores amongst outpatients seeking hand surgical care, albeit in limited populations of 84 and 93 patients at a single center, respectively. 9,13 …”
Section: Introductionmentioning
confidence: 91%